Atypical social cognitive processing in premotor Huntington's disease: a single case study. (26th October 2015) - Burke, T.; Healy, D.; Casey, P.; Hardiman, O.; Pender, N.
Abstract : Background: We report the case of a 52-year-old male with pre-motor Huntington's disease (HD) who has undergone detailed clinical and neuropsychological examination. This patient's negative symptomatology and behavioural change are having a detrimental impact on his social, occupational and interpersonal life, in the absence of motor symptoms. Methods: The patient has undergone repeat neuropsychological testing (T1 aged 50; T2 aged 52) with particular focus on executive function and social cognition on repeat testing. Results: This case details a specific manifestation of HD relating to behavioural, psychiatric and social affective deficits. Conclusions: This case illustrates how social cognitive changes can occur in HD, months and even years prior to the onset of motor features and how such unrecognized deficits can have a deleterious impact on an individual's functional ability and lifestyle, before the disease is traditionally considered to have become manifest.